A retrospective study on potential drug interactions: A single center experience - Fatma Ceyda Korucu; Ece Senyigit; Osman Köstek; Nazım Can Demircan; Bulent Erdogan; Sernaz Uzunoglu; Irfan Cicin (Journal of Oncological Sciences)
Background: In this study, it is aimed to explain the type and frequency of potential drug-drug interactions (pDDI) in patients a Medical oncology service. Methods: This study retrospective descriptive design. pDDIs were identified using the checker programme (Medscape®). Interactions were classified according to their clinical relevance as minor, moderate and major as appropriate. Results: The prevalence of pDDIs was 71.3% and median age was 61 years-old (interquartile range 54–68) and female to male ratio was 116/211. The median number of drugs per patient was 8 (interquartile range 5–10). A total of 1102 pDDIs of 327 hospitalized cancer patients were identified. Of those, 16.7% were major and 61.8% moderate, respectively. Concomitant use of opioids was the most common interaction in our study. Conclusions: Drug interactions were common in hospitalized cancer patients. In order to prevent potential hazardous effect of pDDI, awareness of the physicians should be increased about this issue. Keywords: Cancer patients, Oncology, Polypharmacy, Drug interaction, Chemotherapy